Utilizing Cogni Anki Flash Card : AI-Based Application To Improve Students’ Vocabulary Mastery - Purba, Indra Pranata; Purba, Rudiarman; Marpaung, Tiarma Intan (CV Putra Publisher, 2026)
This study aims to determine the effect of using Cogni Anki Flash Card media on improving vocabulary mastery of eleventh grade students. Cogni Anki Flash Card is a learning tool or application that uses a spaced repetition method to help users remember vocabulary, use it grammatically and vocabulary information more effectively. This study uses a quantitative research design that uses experimental and control classes. The population of this study was eleventh grade students at SMK Negeri 1 Siantar in the 2025/2026 academic year. The researcher took two classes as samples in this study. The sample was XI DKV 1 as a control class consisting of 36 students where this class was only taught using conventional methods. While class XI DKV 2 consisting of 36 was an experimental class that was taught and received treatment from Cogni Anki Flash Card. Data were obtained through pre-tests and post-tests given to students in both classes. Data were analyzed using descriptive statistics, percentage increase in scores, normality and homogeneity tests, paired and independent t-tests, and effect size analysis. The findings revealed significant improvement in the experimental class, with the mean score increasing from 46.39 in the pre-test to 83.06 in the post-test. Based on the post-test classification, 5.6% of students achieved the “excellent” category, 44.5% were in “very good,” and 50.0% were in “good.” In contrast, the control class showed only modest progress, with the mean score increasing from 48.61 to 66.53. The distribution of the post-test results showed that 11.1% of students achieved the “excellent” category, 13.9% were “fair,” 27.8% were “fair,” and 8.3% were “poor.” Statistical analysis through paired and independent t-tests confirmed a significant difference between the two classes. The t-test for effect size calculation (Cohen’s d = 0.74) indicated a moderate effect on students’ vocabulary mastery. Furthermore, the t-test showed a p-value (2-tailed) of 0.000, which is below 0.05. Consequently, the null hypothesis (H₀) is rejected, and the alternative hypothesis (H₁) is accepted since the p-value (0.000) < 0.05. These findings indicate that Anki Flash Cards can be an effective tool to improve students' vocabulary mastery at SMK Negeri 1 Siantar